Unusual metastasis from rectal cancer: case report - Kuliavas, Justas; Dulskas, Audrius; Drachneris, Julius; Mišeikytė Kaubrienė, Edita; Samalavičius, Narimantas E. (Lietuvos chirurgija, 2017)
Metastasis of rectal cancer to the penis is a very rare condition with less than 40 cases found in the literature. The prognosis is poor and life expectancy is short. The mechanism of rectal cancer metastasis spread to penis is unknown. The most popular theory is retrograde venous spread. There are several treatment options, but no single treatment option has emerged with superior results. The authors report a case of a 41 old man who was diagnosed with rectal cancer, treated with neoadjuvant radiotherapy, underwent rectal resection, had adjuvant chemotherapy, and despite that, 2 years after had penal metastasis. After diagnosis, he survived 2 months.